Healthcare Quality Improvement Strategies: A Meta-analysis of Their Impact on Patient Safety and Satisfaction - Jasmin Ambas (Penelitian dan Pengembangan Ilmu, 2024)
Technology-based health service quality improvement strategies aim to increase efficiency, effectiveness and quality of health services. However, key challenges in improving patient satisfaction and safety require further attention. This study aims to evaluate the effectiveness of technology-based strategies in improving patient satisfaction and safety. The research method uses a meta-analysis approach by collecting articles from databases such as Scopus and PubMed, and applying the PRISMA method for filtering articles. The research results show that the use of technology such as wearable devices, artificial intelligence (AI), and the Internet of Things (IoT) has a significant positive impact on patient safety and satisfaction. Implications of this research include recommendations for health policy, clinical practice, training and education, as well as increasing patient involvement in the care process.